Efficacy of Chlorhexidine after Oral Surgery Procedures on Wound Healing: Systematic Review and Meta-Analysis - María de Nuria Romero-Olid; Elena Bucataru; Pablo Ramos-García; Miguel Ángel González-Moles (MDPI AG, 2023)
Our objective was to evaluate qualitatively and quantitatively, through a systematic review and meta-analysis, available evidence on the efficacy of chlorhexidine (CHX) when applied after oral surgery on wound healing and related clinical parameters. MEDLINE/PubMed, Embase, CENTRAL, Web of Science, and Scopus were searched for studies published before January 2023. The quality of the methodology used in primary-level studies was assessed using the RoB2 tool; meta-analyses were performed jointly with heterogeneity and small-study effect analyses. Thirty-three studies and 4766 cases were included. The results point out that the application of CHX was significantly more effective, compared to controls where CHX was not employed, providing better wound healing after oral surgery (RR = 0.66, 95% CI = 0.55-0.80, p < 0.001). Stratified meta-analyses confirmed the higher efficacy of 0.20% CHX gel vs. other vehicles and concentrations (p < 0.001, respectively). Likewise, the addition of chitosan to CHX significantly increased the efficacy of surgical wound healing (p < 0.001). The use of CHX has also been significantly beneficial in the prevention of alveolar osteitis after any type of dental extraction (RR = 0.46, 95% CI = 0.39-0.53, p < 0.001) and has also been effective when applied as a gel for a reduction in pain after the surgical extraction of third molars (MD = −0.97, 95% CI = −1.26 to −0.68, p < 0.001). In conclusion, this systematic review and meta-analysis demonstrate on the basis of evidence that the application of CHX exerts a beneficial effect on wound healing after oral surgical procedures, significantly decreasing the patient's risk of developing surgical complications and/or poor wound healing. This benefit was greater when CHX was used at 0.20% in gel form with the addition of chitosan.